A Pulsed Magnetıc Fıeld Generator Developed For Usıng In Orthodontıc Researches Carrıed On Guınea Pıgs - M. Okan Akçam; Erhan Özdiller; M. Birol Özel; Hüseyin Koru (Galenos Yayinevi, 2000)
In this study, design and implementation of an electronic system that will provide opportunity to investigate the effects of extremely low frequency pulsed magnetic fields on rapid ossification of cartilaginous tissues, is being described. The electronic system produces a 100 Hz pulsed magnetic field of intensity 5.3 milli Tesla (peak) within the cylindrical volume formed by 16 paralelly placed coils separated by 8 centimeters consecutively.